2019
DOI: 10.1002/cam4.2178
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative quantification of meningioma cell proliferation potential using rapid flow cytometry reveals intratumoral heterogeneity

Abstract: Background Standard sampling methods to evaluate the proliferative ability of meningioma have not been established. Methods This prospective study was conducted to evaluate the effectiveness of intraoperative rapid flow cytometry (iFC) using raw samples for the quantitative assessment of proliferative ability in meningioma cells and to investigate intratumoral heterogeneity. Proliferation index (PI) was defined as the ratio of aneuploid cells with an abnormal number of chromosomes to the total cells. Results F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…Another small study of 16 VS cases reported that an MIB-1 LI of 2% or higher was associated with a significantly shorter tumor doubling time [28]. Although one of the advantages of iFC is the high quantitative capability, as shown in our preliminary experiment and previous literature [11][12][13][14][15], our data failed to demonstrate the effectiveness of iFC in assessing the risk of recurrence. This might be because no tumor recurred after gross or near-total resection in our study, suggesting that the extent of resection has greater prognostic significance than the specific proliferative potential in the treatment of VSs.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…Another small study of 16 VS cases reported that an MIB-1 LI of 2% or higher was associated with a significantly shorter tumor doubling time [28]. Although one of the advantages of iFC is the high quantitative capability, as shown in our preliminary experiment and previous literature [11][12][13][14][15], our data failed to demonstrate the effectiveness of iFC in assessing the risk of recurrence. This might be because no tumor recurred after gross or near-total resection in our study, suggesting that the extent of resection has greater prognostic significance than the specific proliferative potential in the treatment of VSs.…”
Section: Discussioncontrasting
confidence: 75%
“…In addition, the recurrence risk of histologically benign tumors should ideally be evaluated prospectively with a larger cohort and a follow-up period of 5-10 years. Third, although previous studies have shown that the PI is correlated with MIB-1 and WHO grading of meningiomas [11,13], the evaluation of the MIB-1 LI is subject to inter-and intra-observer biases inherent to the counting method. Finally, although we unified the location to obtain the cisternal specimen as the center of the portion in this study, there might also be heterogeneity inside the large cisternal portion.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This novel approach enables a faster determination of the MIB-1 index and the proliferative potential intraoperatively [ 44 , 45 ]. Another interesting option to intraoperatively estimate the proliferative potential might be rapid flow cytometry which was found to be significantly correlated with the postoperative MIB-1 index in meningiomas [ 46 ]. Those methods might inform the surgical decision-making process regarding the weighting up the pros and cons of aggressive resection in terms functional preservation and provide a tailored therapy.…”
Section: Discussionmentioning
confidence: 99%